Extratos vegetais e reguladores de crescimento no cultivo in vitro e aclimatização de Miltonia flavescens (Lindl.) Lindl. (Orchidaceae) - Zanella, Samara (2021)
Miltonia flavescens is a native species of the Atlantic Forest, a biome that suffers constant pressure from extractivism, deforestation and predatory collection, making several species of orchids threatened with extinction. Tools that can help in the propagation of these species, such as in vitro propagation, are of fundamental importance because they allow the handling and obtaining of a large quantity of plants in a relatively short space and period of time. One of the most relevant factors for the success of the culture is the composition of the culture medium, to which several compounds can be added, such as growth regulators or plant extracts, which act optimizing the development of cultivated plants and providing conditions that can reflect positively on the survival of plants during acclimatization. Thus, the objective of this work was to elaborate in vitro multiplication and development protocols for Miltonia flavescens using plant extract of ora-pro-nobis (Pereskia aculeata Mill.) and growth regulators (Indolbutyric Acid and Thidiazuron) in order to optimize growth and acclimatization, aiming at possible repopulation programs. Based on the results obtained, the best treatments for the cultivation of the species were with the use of the aqueous extract of ora-pro-nóbis in concentrations of 25% and 50%, and, in the case of growth regulators, with 4 mg.L-1 of AIB that provided greater increments in the variables height of the aerial part, length of the root system and number of roots. The analysis of the root anatomy of the samples demonstrated that the plants of M. flavescens possess capacity of acclimatization to the environment, although the treatments with IBA did not demonstrate greater advantages for the survival of the plants in detriment of the control treatment.